Efforts Towards Development Planning, Issues and Challenges: An Overview of Nigeria Experience - Abubakar S Yushau Alfakoro (Sang Pencerah: Jurnal Ilmiah Universitas Muhammadiyah Buton, 2021)
So essential and imperative is national development plans to the success of any nation. If any country desires to attain sustainable economic growth and development, be it developed or developing, it must make plans for its goals and objectives. Since colonial period and after, Nigeria has committed itself on series of national development plans in order to attain sustainable economic growth and development. It is not a denying fact that Nigeria efforts towards development plans have not been achieved and also improves its economic situation. Over time, this has been proved from economic indicators such as increase in rate of unemployment, short life expectancy ratio, lack of infrastructural facilities and absolute poverty as a result of the spillover effect of its development plans to instill results. The main objective of this research work is to overview some of the previous Nigerian development plans and pin-point out the militating factors that serve as deterrent to the achievement of development plans in the country. This research work sourced its materials through secondary sources of materials. However, competent development expert, corruption free society, political leadership, harmonization and efficient resource allocation are part of the remedies or motor for a successful and sustainable national development plans